The Effect of Population and Human Development Index (IPM) on The Open Unemployment Rate in West Nusa Tenggara Province in 2018-2023 - Ayuwanjani, Selvi Sari; Busaini, Busaini; Purwadinata, Subhan (West Science Social and Humanities Studies, 2025)
This study aims to determine the effect of population and Human Development Index (IPM) on the open unemployment rate in NTB Province in 2018-2023. This study is a quantitative study with an associative approach. In the study, data collection was carried out directly through the Central Statistics Agency (BPS) of NTB Province. Using three data, namely population data, Human Development Index data and open unemployment rate data for NTB Province in 2018-2023. The analysis method used in this study is panel data regression using Eviews 12.0 software. The results of this study indicate that population has a positive and insignificant effect on the open unemployment rate and the Human Development Index (IPM) has a negative and significant effect on the open unemployment rate and simultaneously the population and Human Development Index (IPM) have a significant effect on the open unemployment rate. The implications of these findings indicate that population growth needs to be managed properly so as not to increase the risk of unemployment. In addition, increasing the IPM has been shown to reduce the unemployment rate, so efforts to improve the quality of education, health, and living standards must continue to be encouraged by the local government.